Comparative clinical evaluation of two different techniques of local anaesthesia in the posterior mandible using 4% articaine with 1 : 100,000 adrenaline - Marjanovic, Uroš M; Jurišić, Milan; Brković, Božidar; Jakovljević, Aleksandar; Miličić, Biljana; Marjanović, Marjan; Ivanović, Julija (Vojnosanitetski pregled, 2017)
Background/Aim. Local infiltration anaesthesia (LIA) is significantly simpler compared to the inferior alveolar nerve block (IAB) and less unpleasant for patients. However, it is not efficient if used in posterior region of the mandible, at least with traditional local anaesthetics. The aim of this study was to compare anaesthetic efficacy of two techniques the LIA in the posterior segment of the mandible, and the IAB, using 4% articaine with 1 : 100,000 adrenaline and to note possible changes in haemodynamic parameters caused by these two techniques. Methods. Sixty pre-informed patients were divided into two study groups. Both groups received 1.8 mL of the same anaesthetic solution, 4% articaine with adrenaline 1 : 100,000, with two different techniques of local anaesthesia. The first group received the LIA in projection of root apex of the first lower molar; the second group received the IAB. The examined parameters were: changes in tooth sensitivity after 5 and 30 minutes in relation to the value recorded before administering the anaesthetics, onset of anaesthesia, width of anaesthetic field, and duration of anaesthesia. Also, the impact of the applied techniques on cardiovascular parameters was noticed. Results. The LIA group had a statistically significant decrease in sensitivity 5 minutes after application of the local anaesthetic. The decreasing trend continued between 5 and 30 minutes, although without statistical significance. There was no statistically significant difference in sensitivity changes between two groups for the first molar and the first and second premolars. However, there was a statistically significant difference in duration of local anaesthesia in favour of the IAB, while the width of anaesthetic fields was significantly higher after the LIA. Significant changes in hemodynamic parameters were not recorded within the two groups. Conclusion. The effect of the LIA on tooth sensitivity of premolars and first molar is quite satisfactory. The IAB was more effective for canine and second molar. None of the tested techniques had any significant effect on the cardiovascular parameters.